2000
DOI: 10.1097/00007890-200009150-00004
|View full text |Cite
|
Sign up to set email alerts
|

l-ARGININE REDUCES LIVER AND BILIARY TRACT DAMAGE AFTER LIVER TRANSPLANTATION FROM NON-HEART-BEATING DONOR PIGS1

Abstract: L-Arginine administration during liver procurement from non heart beating donors prevents liver and biliary tract damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Though the basic details of the transplant procedure were the same, the 130 transplants were ultimately performed according to one of four experimental transplant models: standard, whole-liver transplant (n ¼ 10), small-forsize liver transplant (n ¼ 48) [20], donor after cardiac death (DCD) liver transplant (n ¼ 44), and liver transplant following adenoviral gene transfection in the donor (n ¼ 28) [19]. For all of the transplant procedures, the average cold ischemic time was 302 6 43 min and anhepatic time 17 6 3 min (range [10][11][12][13][14][15][16][17][18][19][20][21][22]. No incidences of vascular thrombosis, venous outflow obstruction, or bile duct dehiscence were discovered at autopsy or euthanasia in any of the recipients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the basic details of the transplant procedure were the same, the 130 transplants were ultimately performed according to one of four experimental transplant models: standard, whole-liver transplant (n ¼ 10), small-forsize liver transplant (n ¼ 48) [20], donor after cardiac death (DCD) liver transplant (n ¼ 44), and liver transplant following adenoviral gene transfection in the donor (n ¼ 28) [19]. For all of the transplant procedures, the average cold ischemic time was 302 6 43 min and anhepatic time 17 6 3 min (range [10][11][12][13][14][15][16][17][18][19][20][21][22]. No incidences of vascular thrombosis, venous outflow obstruction, or bile duct dehiscence were discovered at autopsy or euthanasia in any of the recipients.…”
Section: Resultsmentioning
confidence: 99%
“…Since the mid 1990s, our group has used a simplified technique to perform hundreds of liver transplants in pigs with consistent success [15][16][17][18][19][20]. The purpose of this work is to communicate, in detail, how to reproduce this technically straightforward model, from the induction of anesthesia to the postoperative follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that survival was closely related to persistence of a good hepatic blood flow (12,35,36). The better the blood flow obtained during NR the better the survival, suggesting that preservation of the vascular bed is a key point in organ viability.…”
Section: Discussionmentioning
confidence: 99%
“…101 For NHBD, machine perfusion with the addition of pentoxifylline or arginine to perfusion solutions may also improve the quality of these grafts by reversing ischemic damage. 102,103 Hypernatremia was shown by the UCLA group to be one of five variables with prognostic value in predicting graft survival after transplantation. 28 The mechanism for the deleterious effect of elevated donor sodium on graft function is thought to be a result of cell swelling and exacerbation of reperfusion-mediated injury.…”
Section: Experimental Strategies For the Manipulation Of Marginal Donorsmentioning
confidence: 99%